Assessment of the impact of seasonal patterns climatic conditions on spawning events of the white bream Blicca bjoerkna (Linnaeus, 1758) in astronomical and biological time - D. Bondarev; O. Kunakh; O. Zhukov (Acta Biologica Sibirica, 2018)
This paper describes spawning events of the white bream Blicca bjoerkna (Linnaeus, 1758 )in astronomical and biological time depending on seasonal patterns of climatic conditions. The research was conducted in the "Dnipro-Orilskiy" Nature Reserve (Ukraine) during the years 1997–2015 in four habitat types. The timing of the spawning event (start, end) was evaluated using astronomical time (number of days from January 1 each year), with correction for the lunar and the semilunar cycle, and using biological time (number of days from the end of spawning in the previous year to the beginning and end of spawning in the current year). The spawning phenology of the white bream was found to be dependent on the dynamics of weather conditions over time. Patterns of varying climatic regimes which are expressed by means of multivariate principal component are the most informative predictors of the spawning events. Evaluation of occurrence of spawning events in astronomic or biological time gives somewhat different models of the impact of climate regimes. The impact of the principal components indicating variability of rainfall during the year in which spawning occurs is statistically significant for almost all regression models. Models using the solar calendar are also more sensitive to the course of air temperatures within the year when spawning occurred. Correction of time based on the lunar cycle allows us to assess events which are sensitive also to the temperature and rainfall variation during the second half of the previous year. Biological time was shown to be sensitive to environmental influences over time from the end of spawning in the previous year to spawning in any given year.